2017
DOI: 10.1016/j.engfracmech.2016.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Damage onset modeling in woven composites based on a coupled stress and energy criterion

Abstract: International audienceThe crack onset configuration at damage onset in a four-layer plain weave glass fiber/epoxy matrix composite is studied at the mesoscopic scale using a coupled criterion based on both a stress and an energy condition. The possible crack shapes are selected based on optical microscope observations of damage mechanisms on a specimen edge during a tensile test. The crack location, length and orientation, the decohesion length and the strain at damage onset are determined. The damage onset st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 41 publications
(78 reference statements)
1
42
0
Order By: Relevance
“…This is not the case employing CZM, which requires several calculations with varying G c and σ c to be computed. Conversely, in the case where several crack configurations have to be studied for given fracture parameters, the number of calculations to perform in order to solve the CC exponentially increases with the number of parameters describing the crack [9]. In this case, the CZM can be a powerfull approach since it allows taking into account, for instance, different crack paths in a single computation, obviously leading to more costly computations due to an increase in the number of dof and more restrictive convergence conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not the case employing CZM, which requires several calculations with varying G c and σ c to be computed. Conversely, in the case where several crack configurations have to be studied for given fracture parameters, the number of calculations to perform in order to solve the CC exponentially increases with the number of parameters describing the crack [9]. In this case, the CZM can be a powerfull approach since it allows taking into account, for instance, different crack paths in a single computation, obviously leading to more costly computations due to an increase in the number of dof and more restrictive convergence conditions.…”
Section: Discussionmentioning
confidence: 99%
“…1 shows the case of a non monotonic variation of G inc , i.e. G inc attains a maximum for a crack surface S m [9,29,42]. In most cases, crack initiation surface verifies S * < S m (Fig.…”
Section: G(s)mentioning
confidence: 99%
See 1 more Smart Citation
“…Damage initiation in woven composites is generally modeled using a stress-based criterion [9,10,11,12,19,23], which gives a good estimate of the crack locations [19,23,24]. However, the damage initiation strain is underestimated if only a stress criterion is used and a better estimate is obtained [24] if energetic considerations based on Finite Fracture Mechanics (FFM) [31] are also taken into account, as proposed by Leguillon [32], for instance. In a previous work [24], it has been shown that, in the studied composite, the energy criterion is dominant and thus Finite Fracture Mechanics can be used to accurately model the initiation of yarn cracks.…”
Section: Introductionmentioning
confidence: 99%
“…However, the damage initiation strain is underestimated if only a stress criterion is used and a better estimate is obtained [24] if energetic considerations based on Finite Fracture Mechanics (FFM) [31] are also taken into account, as proposed by Leguillon [32], for instance. In a previous work [24], it has been shown that, in the studied composite, the energy criterion is dominant and thus Finite Fracture Mechanics can be used to accurately model the initiation of yarn cracks. Moreover, it also allows for the determination of the crack initiation configuration (e.g., length, orientation).…”
Section: Introductionmentioning
confidence: 99%